2008
DOI: 10.1111/j.1469-8137.2008.02568.x
|View full text |Cite
|
Sign up to set email alerts
|

A study on the susceptibility of rice cultivars to Striga hermonthica and mapping of Striga tolerance quantitative trait loci in rice

Abstract: Summary• Striga is a parasitic weed attacking mainly maize, sorghum, millet and cowpea. Studying the interaction between rice and Striga is valuable since rice is a model monocot. In this paper, the susceptibility of different rice cultivars to S. hermonthica was tested and quantitative trait loci (QTL) for Striga tolerance mapped on the Bala × Azucena F 6 population.• Seven rice cultivars were grown with and without S. hermonthica for 14 wk. For the mapping experiment, 115 recombinant inbred lines (RILs), alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 22 publications
(37 reference statements)
2
23
1
Order By: Relevance
“…The later establishment of infection in Azucena likely explains the higher tolerance to Striga, similar to what was observed in sorghum, where tolerant varieties generally exhibit later Striga emergence (40). Intriguingly, Striga postattachment resistance mapped to the same position on chromosome 1 as the QTL discussed in the present work (near marker C1370) in a cross between Nipponbare and Kasalath (21), with the Nipponbare allele conferring greater resistance (41). Nipponbare contains the same allele as Azucena, and we confirmed that Kasalath carries the same allele as Bala for the locus under study.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…The later establishment of infection in Azucena likely explains the higher tolerance to Striga, similar to what was observed in sorghum, where tolerant varieties generally exhibit later Striga emergence (40). Intriguingly, Striga postattachment resistance mapped to the same position on chromosome 1 as the QTL discussed in the present work (near marker C1370) in a cross between Nipponbare and Kasalath (21), with the Nipponbare allele conferring greater resistance (41). Nipponbare contains the same allele as Azucena, and we confirmed that Kasalath carries the same allele as Bala for the locus under study.…”
Section: Discussionsupporting
confidence: 55%
“…However, although decreased SL biosynthesis results in less Striga germination, it is unclear whether SL levels also affect Striga attachment. In earlier work, Striga tolerance mapped to the same region as qSLB1.1, with the Azucena allele increasing Striga tolerance (21), even though in the present study we showed there were more Striga emerging on Azucena in controlled environments (Fig. 1A).…”
Section: Discussioncontrasting
confidence: 36%
See 2 more Smart Citations
“…Gurney et al (2006) Gurney et al (2006). However, in the study conducted by Kaewchumnong and price (2008) on rice cultivars tolerance to Striga showed that the QTL for all rice traits in the Striga infected were present between position 139 and 169 cM on chromosome 1. The QTL LOD scores ranged from 4.9 to 15.7 and they were significant at 3.2.…”
Section: Conditions Favoring Striga Growthmentioning
confidence: 99%